2020
DOI: 10.1186/s40643-020-00352-4
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient production of an influenza H9N2 vaccine using MDCK suspension cells

Abstract: The use of H9N2 subtype avian influenza vaccines is an effective approach for the control of the virus spread among the poultry, and for the upgrading of vaccine manufacturing, cell culture-based production platform could overcome the limitations of conventional egg-based platform and alternate it. The development of serum-free suspension cell culture could allow even higher virus productivity, where a suspension cell line with good performance and proper culture strategies are required. In this work, an adher… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…An MDCK suspension cell line (ATCC CCL‐34 origin) adapted to grow in suspension in a serum‐free medium (Huang et al, 2011, 2015; Wu et al, 2020), was cultivated in a newly developed chemically defined medium, referred as “Xeno‐CDM” (Shanghai BioEngine Sci‐Tech). For media adaptation to Xeno‐CDM the medium proportion was increased by 25% steps for four passages, with no apparent changes in cell line performance.…”
Section: Methodsmentioning
confidence: 99%
“…An MDCK suspension cell line (ATCC CCL‐34 origin) adapted to grow in suspension in a serum‐free medium (Huang et al, 2011, 2015; Wu et al, 2020), was cultivated in a newly developed chemically defined medium, referred as “Xeno‐CDM” (Shanghai BioEngine Sci‐Tech). For media adaptation to Xeno‐CDM the medium proportion was increased by 25% steps for four passages, with no apparent changes in cell line performance.…”
Section: Methodsmentioning
confidence: 99%
“…Another study reported generation of an H9 virus-like-particle vaccine using a non-egg-based platform [ 32 ]. Traditionally, vaccines against avian influenza viruses are derived from influenza isolates grown by multiple passage in embryonated chicken eggs; this results in high yield strains, which are then inactivated and delivered with mineral oil adjuvant [ 2 , 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%